Implementation of Management Functions (POAC) in the MSME Empowerment Program at the Ministry of Cooperatives and Small and Medium Enterprises - Edlyn Salsabella; Lutfia Lukinita; Kayla Azzahra Berlandy; Fasihah Habibah Aulia; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (Income Journal Of Economics Development, 2026)
MSME empowerment is one of the important strategies in the government to improve the national economy and increase the competitiveness of small businesses in the midst of increasingly fierce market competition. To run it successfully, organized program management is essential. One of the approaches used is the POAC management function, which means planning, organizing, actuating, and controlling. This function is responsible for ensuring that the program runs systematically and in a directional manner.  Using a descriptive qualitative method, this study aims to evaluate the application of POAC in the MSME empowerment program at the Ministry of Cooperatives and Small and Medium Enterprises. This study uses a descriptive qualitative approach to evaluate the implementation of Planning, Organizing, Actuating, and Controlling (POAC) in MSME empowerment programs at the Ministry of Cooperatives and SMEs. Data were collected through observation and document analysis, then examined using an interactive analysis model and data triangulation. The study identifies gaps between planning and implementation and provides recommendations to improve program coordination, accountability, and monitoring. The results show that the implementation of POAC is quite good and has a positive effect, especially on training, financing, and digitalization of MSMEs. However, there are obstacles such as a lack of supervision systems, poor coordination, and planning that is not yet data-driven.